2012
DOI: 10.1021/ci300299n
|View full text |Cite
|
Sign up to set email alerts
|

Study ofE/ZIsomerization in a Series of Novel Non-ligand Binding Pocket Androgen Receptor Antagonists

Abstract: We report the conformational analysis of a series of 3-hydroxy-N′-((naphthalen-2-yl)methylene)naphthalene-2-carbohydrazides. This class of compounds has recently been reported as androgen receptor (AR)-coactivator disruptors for potential application in prostate cancer therapy. Definition of the E/Z isomerism around the imine linker group (hydrazide) is significant from a mechanistic point of view. A detailed study using theoretical calculations coupled with experimental techniques has allowed us determine an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Under these conditions, the E-isomer of the CN is obtained almost quantitatively, as it was proven by a spectroscopic and theoretical study. 34 Biological Evaluation of AR Modulation. Measurement of AR Antagonistic Activity -AR TR-FRET Assays.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, the E-isomer of the CN is obtained almost quantitatively, as it was proven by a spectroscopic and theoretical study. 34 Biological Evaluation of AR Modulation. Measurement of AR Antagonistic Activity -AR TR-FRET Assays.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A number of derivatives were chemically characterized and subjected to biological evaluation. 33,34 Among these derivatives, compounds 1−5 ( Figure 2) showed AR antagonistic activity by TR-FRET analysis, and a non-LBP mechanism of action was confirmed by FP assays. Interestingly, many other derivatives of the same family were inactive (6−25) under identical conditions.…”
Section: ■ Introductionmentioning
confidence: 93%
“…5 This ring closure likely occurs via hydrazone to diazene tautomerism as illustrated in Scheme 1. 12 Hydrazones of 3-carboethoxy-4-acetyl-isoxazole had previously been prepared without observation of ring closure, and crystallographic characterization showed that they adopted the E-double bond geometry at the C=N of the hydrazone. 13 Reaction to the isoxazolo[3,4- d ]pyridazinone requires the Z-geometry, which can most reasonably be attained via the intermediacy of the diazene tautomer.…”
mentioning
confidence: 99%
“…The crystal structures reported here cannot be compared to literature data, since no chiral secondary aldimine bearing a 2-naphthyl group on the C-side have been X-ray characterized up to now, and only a few cases are available with substituted naphthyl groups, generally related to BINOL derivatives (Li et al, 2004). However, small achiral Schiff bases including naphthyl (Blanco et al, 2012), or naphthol (Ferná ndez-G et al, 1995, 2001Martínez et al, 2011) have been reported. For these crystal structures, a general propensity to form C-HÁ Á Á intermolecular contacts rather thancontacts is observed.…”
Section: Supramolecular Featuresmentioning
confidence: 82%